2020
DOI: 10.7150/ijms.47067
|View full text |Cite
|
Sign up to set email alerts
|

Sedation and Analgesia for Liver Cancer Percutaneous Radiofrequency Ablation: Fentanyl and Oxycodone Comparison

Abstract: Background: Sedation and analgesia use in percutaneous radiofrequency ablation (RFPA) for liver cancer is a necessary part of the procedure; however, the optimal medicine for sedation and analgesia for PRFA remains controversial. The aim of this study was to compare the perioperative pain management, haemodynamic stability and side effects between oxycodone (OXY) and fentanyl (FEN) use in patients under dexmedetomidine sedation. Methods: Two hundred and five adults with an American Society of Anaesthesiologist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(33 reference statements)
0
4
1
Order By: Relevance
“…Previous studies have demonstrated that tumor characteristics such as location, type or size are known risk factors for the occurrence of periprocedural pain [6,7,9,10,27]. In our study, tumor characteristics did not predict post-ablation pain.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…Previous studies have demonstrated that tumor characteristics such as location, type or size are known risk factors for the occurrence of periprocedural pain [6,7,9,10,27]. In our study, tumor characteristics did not predict post-ablation pain.…”
Section: Discussioncontrasting
confidence: 66%
“…The latter association is also not noted in our study, suggesting a limited effect of tumor type on post procedural pain intensity. One explanation might be that PSA strategies differ between the studies [6,7,9,10]. The depth of sedation varied from light to moderate and moderate to deep.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Respiratory events due to poor oxygen supply or ventilation are the most common adverse events during extra-operative anesthesia [23]. Activation of µ-opioid receptors in the central nervous system is associated with adverse effects such as over-sedation, respiratory depression and PONV [24].Esketamine stimulates breathing through increasing carbon dioxide sensitive ventilation [23].Studies by Drummond et al on lingual muscle activity and airway obstruction during sedation with Midazolam and Ketamine showed that Ketamine had a bene cial effect on airway patency [25]. There were more patients with respiratory depression in Group S than in Group E. Three patients in Group S and one patient in Group E. The comparison between the two groups was not statistically signi cant.…”
Section: Discussionmentioning
confidence: 99%